`Future Events we unto thee impart': A Transatlantic Examination of Almanacs in the Seventeenth and Eighteenth Centuries. - Hudson, Madeleine. (2017)
Abstract: Almanacs in the seventeenth and eighteenth centuries in England and the British North American colonies acted as a daily reference guide for readers. This thesis closely examines case studies on both sides of the Atlantic during this period in order to study the transatlantic development of almanacs. It argues that colonial American almanacs drew upon traditional English almanac format and content, but developed their own style. This new American form of the genre was based upon the need of colonial readers for a cheaper, shorter almanac, that almanac authors still needed to make appealing for buyers even as they cut down on the amount of content that they included. In conclusion, this study, by closely examining the almanac series of multiple authors in England and the colonies, sheds new light on the transatlantic influences and development of this genre.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of History.; Advisor: Alisha Rankin.; Committee: Ina Baghdiantz McCabe, and Christopher Schmidt-Nowara.; Keywords: History, American history, and European history.